Multiple Levels of Bilingual Language Control: Evidence From Language Intrusions in Reading Aloud. (February 2014) - Gollan, Tamar H.; Schotter, Elizabeth R.; Gomez, Joanne; Murillo, Mayra; Rayner, Keith
Bilinguals rarely produce words in an unintended language. However, we induced such intrusion errors (e.g., saying el instead of he ) in 32 Spanish-English bilinguals who read aloud single-language (English or Spanish) and mixed-language (haphazard mix of English and Spanish) paragraphs with English or Spanish word order. These bilinguals produced language intrusions almost exclusively in mixed-language paragraphs, and most often when attempting to produce dominant-language targets (accent-only errors also exhibited reversed language-dominance effects). Most intrusion errors occurred for function words, especially when they were not from the language that determined the word order in the paragraph. Eye movements showed that fixating a word in the nontarget language increased intrusion errors only for function words. Together, these results imply multiple mechanisms of language control, including (a) inhibition of the dominant language at both lexical and sublexical processing levels, (b) special retrieval mechanisms for function words in mixed-language utterances, and (c) attentional monitoring of the target word for its match with the intended language.